Non-steroidal hormonal levels during ante and post-partum periods in goats - LEELA, V; SUGANYA, G; THANGAVEL, A; VISWANATHAN, S (The Indian Journal of Animal Reproduction, 2023)
Estimations of T3’ T4, insulin, growth hormone were carried out in twelve Tellicherry goats by RIA. Results indicated that T3 and T4 were increased on the day of parturition and there after. The insulin showed a declining trend up to 10 day after postpartum, whereas the growth hormone showed a steady increase from day preparturn till 15th day parturitio.